IMPLEMENTATION OF CHARACTER EDUCATION AT THE BASIC EDUCATION LEVEL: A SYSTEMATIC LITERATURE REVIEW - Abdillah, Lucky Rafli (Universitas Negeri Malang, 2024)
Abstract Education is an important foundation in human life, as explained in Law No. 20 of 2003 concerning the National Education System, that